VD_FINDINFO Jug / 2017 / 28 vom 17. Mai 2016 - VD Tribunal cantonal (2016)
VIOL, ENLÈVEMENTINFRACTION, LÉSION CORPORELLE SIMPLE, MENACEDROIT PÉNAL, CONTRAINTEDROIT PÉNAL, TENTATIVEDROIT PÉNAL, APPROPRIATION ILLÉGITIME, INJURE, VOLDROIT PÉNAL, CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE, ALCOOLÉMIE, LOI FÉDÉRALE SUR LES ARMES, LES ACCESSOIRES D'ARMES ET LES MUNITIONS | 123 ch. 1 al. 1 CP, 123 ch. 1 al. 2 CP, 137 ch. 1 CP, 139 ch. 1 CP, 172ter CP, 177 al. 1 CP, 177 CP, 180 al. 1 CP, 181 CP, 19 al. 2 CP, 19 CP, 190 al. 1 CP, 22 al. 1 CP, 22 CP, 34 CP, 40 CP, 47 CP, 49 al. 1 CP, 49 CP, 63 CP, 69 CP, 33 al. 1 LArm, 90 al. 1 LCR, 91 al. 1 LCR, 91 al. 2 LCR, 91a al. 1 LCR, 92 al. 1 LCR, 94 ch. 1 al. 1 LCR, 95 al. 1 let. a LCR, 95 ch. 2 LCR, 96 ch. 2 LCR